EVALUATION OF MINERAL-BASED HYDROXYAPATITE/ZnO COMPOSITES AS PHOTOCATALISTS FOR METHYLEN BLUE DEGRADATION - Hardian, Arie; Nafisah, Aulia Zakiyatun; Karya, Teguh; Halim, Riyan; Murniati, Anceu; Syarif, Dani Gustaman; Noviyanti, Atiek Rostika; Nurhayati, Mita; Jasmansyah, Jasmansyah; Reza, Muhammad (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
The use of dyes in the textile industry has increased significantly, raising concerns about their potential to pollute the environment and harm human health. Methylene blue is a widely used synthetic dye, necessitating effective methods for its degradation. Photodegradation is a promising approach to decompose dyes into simpler, less harmful compounds. In this study, hydroxyapatite combined with ZnO was employed as a photocatalyst material to enhance photocatalytic performance. The research aims to degrade methylene blue using a Hydroxyapatite/ZnO (HAp/ZnO) nanocomposite through photodegradation. The optimization of the photodegradation process was investigated by varying irradiation time, methylene blue concentration, and pH. The optimum degradation of methylene blue was achieved using 20 mg of HAp/ZnO nanocomposite at an irradiation time of 120 minutes, an initial methylene blue concentration of 5 ppm, and pH 7. Adsorption isotherm modeling revealed that the process followed the Langmuir isotherm model, with a maximum adsorption capacity (qmax) of 0.3353 mg/g. The degradation followed pseudo-second-order kinetics with a reaction rate constant of 4.0026×105 L/mol·s.